Improving Knowledge Management for Better Competitive Advantage Through Strategy Execution - Wirawan Tedja (Research Synergy Foundation, 2022)
Based on previous studies, the relationship between knowledge management and competitive advantage has not reached a conclusive result. Therefore, this study aims to lay a theoretical foundation for the relationship between knowledge management and competitive advantage while taking into account the mediating role of strategy execution. We utilise Resource-Based Theory and knowledge management as our basis to explore this relationship. We also propose propositions and reasoning for every relationship discussed in this study based on theories and previous studies. In the end, we provide a theoretical research model for any researchers interested in exploring this proposal in various contexts, both empirically and theoretically. We proposed a novel theoretical perspective in exploring knowledge management theory by providing this model.